Investigating body composition and body mass index using oral hypoglycemic agents and insulin therapy in type 2 diabetes mellitus - Husna, Cut; Darmawati, Darmawati; Firdausa, Sarah; Ahyana, Ahyana; Nurhidayah, Irfanita (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Type 2 diabetes mellitus (T2DM) is increasingly prevalent worldwide, and pharmacological therapy is essential for glycemic control. Insulin therapy (IT) and oral hypoglycemic agents (OHA) are commonly used, but they may have different effects on body composition. This study aimed to compare body composition between patients with T2DM receiving IT and those receiving OHA. Methods: A comparative cross-sectional study was conducted among 314 patients with T2DM at a tertiary hospital in Banda Aceh, Indonesia. Participants were divided equally into IT and OHA groups (n=157 each). Body composition was assessed using bioelectrical impedance analysis, and data were analyzed using independent t-tests, and multiple linear regression. Results: Patients treated with IT had significantly higher body weight, BMI, body fat, muscle mass, bone mass, muscle quality score, physique rating, and visceral fat compared with those on OHA (all p<0.05). No significant differences were observed in basal metabolic rate, metabolic age, total body water, or body height. Regression analysis showed that BMI and gender were the strongest predictors of body fat, muscle mass, and visceral fat, while age was associated with muscle quality and metabolic age. Conclusion: Insulin therapy in patients with T2DM was associated with higher adiposity and altered body composition compared with OHA use. Routine monitoring of body composition and targeted lifestyle interventions should be integrated into the management of T2DM patients receiving insulin.